Armed conflicts in South Asia 2009: continuing violence, failing peace processes - Chandran, D. Suba. (ed.); Chari, P.R. (ed.) (New Delhi, 2010)
The essays in this volume are concerned with armed conflicts in South Asia and the conflict management efforts made to mitigate them. Articles in the volume study conflict management, look at the direction armed conflict is likely to take and provide a set of alternative measures that could be perused by the actors. It addresses five key issues: history of the armed conflict, identifying the principal actors of the conflict, describing the course of the conflict and its major trends, evaluating conflict management measures undertaken, if any, presenting appropriate conclusions. It also includes additional chapters on Naxalism and sectarian strife in Pakistan. Designed as an annual series, this important collection discusses India$1 (Bs geo-strategic importance including its common borders with its neighbours; the psychological and economic costs of violence, and the problem of refugee migrants; treaties and ceasefire agreements signed across countries; the role of the UN and other peacekeeping forces; and the future of failed and failing democracies. The book makes an important contribution to analysing armed conflicts and conflict resolution.s
Keywords: Conflict - South Asia